Juridical Review of the Role of Medan City Bawaslu in Preventing and Monitoring Political Money Practices in the 2024 Election in Medan City - Hisar Siregar; Nalom Siagian; Herlina Manullang; Misefa Harefa (Dinasti Research, 2025)
Indonesia is a country that adheres to a democratic system, which means that the supreme power is in the hands of the people and the people have the right to determine who becomes their leader or representative, through an election, hereinafter referred to as (Election). As stated in Article 1 paragraph (2) of the Constitution of the Republic of Indonesia that